Dialogue between Staphylococcus aureus SA15 and Lactococcus garvieae strains experiencing oxidative stress - Clothilde Queiroux (BMC Microbiology, 2018)
Abstract Background Staphylococcus aureus is an important foodborne pathogen. Lactococcus garvieae is a lactic acid bacterium found in dairy products; some of its strains are able to inhibit S. aureus growth by producing H2O2. Three strains of L. garvieae from different origins were tested for their ability to inhibit S. aureus SA15 growth. Two conditions were tested, one in which H2O2 was produced (high aeration) and another one in which it was not detected (low aeration). Several S. aureus genes related to stress, H2O2-response and virulence were examined in order to compare their level of expression depending on the inoculated L. garvieae strain. Simultaneous L. garvieae H2O2 metabolism gene expression was followed. Results The results showed that under high aeration condition, L. garvieae strains producing H2O2 (N201 and CL-1183) inhibited S. aureus SA15 growth and impaired its ability to deal with hydrogen peroxide by repressing H2O2-degrading genes. L. garvieae strains induced overexpression of S. aureus stress-response genes while cell division genes and virulence genes were repressed. A catalase treatment partially or completely restored the SA15 growth. In addition, the H2O2 non-producing L. garvieae strain (Lg2) did not cause any growth inhibition. The SA15 stress-response genes were down-regulated and cell division genes expression was not affected. Under low aeration condition, while none of the strains tested exhibited H2O2-production, the 3 L. garvieae strains inhibited S. aureus SA15 growth, but to a lesser extent than under high aeration condition. Conclusion Taken together, these results suggest a L. garvieae strain-specific anti-staphylococcal mechanism and an H2O2 involvement in at least two of the tested L. garvieae strains.